Invasive Streptococcus suis isolated in Spain contain a highly promiscuous and dynamic resistome - Uruén, Cristina; Gimeno, Jorge; Sanz, Marina; Fraile, Lorenzo; Marín, Clara M.; Arenas, Jesús (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Streptococcus suis is a major pathogen for swine and human. Here we aimed to know the rates of antimicrobial resistance (AMR) in invasive S. suis isolates recovered along Spain between 2016 – 2021 and elucidate their genetic origin. Methods Antibiotic susceptibility testing was performed for 116 isolates of different genetic backgrounds and geographic origins against 18 antibiotics of 9 families. The association between AMR and genotypes and the origin of the isolates were statistically analyzed using Pearson´s chi-square test and the likelihood ratio. The antimicrobial resistant genes were identified by whole genome sequencing analysis and PCR screenings. Results High AMR rates (>80%) were detected for tetracyclines, spectinomycin, lincosamides, and marbofloxacin, medium (20-40%) for sulphonamides/trimethoprim, tiamulin, penicillin G, and enrofloxacin, and low (< 20%) for florfenicol, and four additional β-lactams. The occurrence of multidrug resistance was observed in 90% of isolates. For certain antibiotics (penicillin G, enrofloxacin, marbofloxacin, tilmicosin, and erythromycin), AMR was significantly associated with particular sequence types (STs), geographic regions, age of pigs, and time course. Whole genome sequencing comparisons and PCR screenings identified 23 AMR genes, of which 19 were previously reported in S. suis (aph(3’)-IIIa, sat4, aadE, spw, aac(6’)-Ie-aph(2’’)-Ia, fexA, optrA, erm(B), mef(A/E), mrs(D), mph(C), lnu(B), lsa(E), vga(F), tet(M), tet(O), tet(O/W/32/O), tet(W)), and 4 were novel (aph(2’’)-IIIa, apmA, erm(47), tet(T)). These AMR genes explained the AMR to spectinomycin, macrolides, lincosamides, tiamulin, and tetracyclines. Several genes were located on mobile genetic elements which showed a variable organization and composition. As AMR gene homologs were identified in many human and animal pathogens, the resistome of S. suis has a different phylogenetic origin. Moreover, AMR to penicillin G, fluoroquinolones, and trimethoprim related to mutations in genes coding for target enzymes (pbp1a, pbp2b, pbp2x, mraY, gyrA, parC, and dhfr). Bioinformatic analysis estimated traits of recombination on target genes, also indicative of gene transfer events. Conclusions Our work evidences that S. suis is a major contributor to AMR dissemination across veterinary and human pathogens. Therefore, control of AMR in S. suis should be considered from a One Health approach in regions with high pig production to properly tackle the issue of antimicrobial drug resistance.